ICOS ATC/CAL Flask Release from Svartberget (150.0 m) - Eric Larmanou; Per Marklund; Paul Smith (Integrated Carbon Observation System, 2025)
can contain atmospheric composition data for any of a number of gases; the data can be a mole fraction, isotope ratio, or other related quantity
Larmanou, E., Marklund, P., Smith, P. (2025). ICOS ATC/CAL Flask Release from Svartberget (150.0 m), 2020-02-29–2025-02-14, ICOS RI, https://hdl.handle.net/11676/X4YxZGxIaVRgjAh1qagfVvsa
Keywords: Atmosphere Thematic Centre; Flask; ICOS; time instant, UTC; time instant, UTC; SF6 (dry air mole fraction); SF6 (dry air mole fraction); standard deviation; standard deviation; number of points; number of points; quality flag; quality flag; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap